Reduction of Central-line–Associated Bloodstream Infections in a Tertiary Neonatal Intensive Care Unit through Simulation Education. Issue 6 (18th November 2022) - Hightower, Hannah B.; Young, John Andrew; Thomas, Jennifer; Smith, Jill Jones; Hobby-Noland, Delphene; Palombo, Georgina; McCaskey, Marjorie; Benton, Beth; Hutto, Cecelia; Coghill, Carl; McCullough, Becky; Hayes, Leslie; et al.
Abstract : Introduction: Critically ill neonates and those with complex medical conditions frequently require the use of central venous lines. Unfortunately, central line-associated bloodstream infections (CLABSIs) result in significant morbidity and mortality, and the cost and increased length of stay burden the healthcare system. Previous studies have demonstrated that standardized care bundles can decrease CLABSI rates, but achieving sustained improvement has proven difficult. Methods: All patients admitted to the Neonatal Intensive Care Unit between 2014 and 2020 who had a CVL were included in this study. First, we recorded all CLABSI events and total CVL days according to defined criteria. Then, in late 2016, we instituted simulation-based nursing training for CVL care. Results: Job Instruction Sheets were initially introduced to Neonatal Intensive Care Unit nursing staff simultaneously with one-on-one teaching sessions between instructors and bedside nurses. Intermittent performance audits and re-education for identified deficiencies did not improve the CLABSI rate per 1000 line days. After instituting simulation-based CVL training in 2016, there was a decreased rate of CLABSI events per 1000 line days sustained over time (x = 0.692). Conclusions: Standardized care bundles and Hospital-acquired Condition interactor audits were insufficient to reduce the CLABSI rate. However, combining care bundles and education with simulation-based training significantly decreased CLABSI rates. One-on-one intensive training and continued ongoing monitoring were critical to producing a sustained reduction. This experience demonstrates that supervised, interactive education combined with simulation can significantly impact patient outcomes.